(untitled) (CAHIERS MAGELLANES-NS, 2024)
Ut l z ng a manual attendance system can pose significant chal enges for preceptors. To al eviate this issue, an intell gent and automated attendance management system is being implemented. This system effectively addresses concerns such as delegates and scholars being marked present erroneously when they are absent physically. Through the ut l zation of live video stream, attendance is recorded seamlessly. Frames extracted from the video stream are processed using OpenCV. The primary methodology employed involves face detect on and recognition, ut iz ng d ib. Subsequently, the identification of recognized faces is established by comparing them with a database containing students' facial data. This approach represents a promising solut on for efficient attendance management